HYPOCENTER DISTRIBUTION OF LOW FREQUENCY EVENT AT PAPANDAYAN VOLCANO - Hasan, Muhammad Mifta; Triastuty, Hetty; Santosa, Bagus Jaya; Widodo, Amien (Jurnal Neutrino, 2016)
Papandayan volcano is a stratovolcano with irregular cone-shaped has eight craters around the peak. The most active crater in Papandayan is a Mas crater. Distribution of relocated event calculated using Geiger Adaptive Damping Algorithm (GAD) shows that the epicenter of the event centered below Mas crater with maximum rms 0.114. While depth of the hypocenter range between 0-2 km and 5-6 km due to activity of steam and gas.